Pengembangan Media Pembelajaran Berbasis Design Animaker pada Materi Pengetahuan Dasar Pemetaan, SMA/MA Kelas X - Ilzam, Moch; Sri Astutik; Era Iswara Pangastuti; Elan Artono Nurdin; Asyroful Mujib (Geography Education Study Program, Universitas Kanjuruhan Malang, 2024)
The rapid and limitless development of information technology marks the era of technology and media. However, the constraint of instructional time often poses a challenge for teachers utilizing technology-based learning media. This research aims to develop and validate a geography learning media based on the Animaker application for high school students, particularly focusing on basic mapping concepts. Using the ADDIE model, the study was conducted at MAN 2 Jember during the academic year 2022/2023, targeting X IPS grade students. Data collection involved student needs surveys, validation of content and media by experts, and student feedback on the learning media. The study developed a video-based geography learning media using Animaker for SMA/MA students, involving a sample of 45 X IPS grade students. The analysis phase included administering student needs surveys, which indicated a majority requirement for learning media. The design of the Animaker application focused on layout, characters, and learning material presentation. Validation by media, content, and educational experts showed valid average scores across all evaluation aspects. Implementation in X IPS 3 and X IPS 4 classes yielded positive student responses, with average ratings of 4.28 for the large group and 4.38 for the small group. Evaluation indicated that the learning media was well-received by students, demonstrating readiness for broader application.